Nonreciprocal acoustic transmission through dynamic multilayer structures - A. Paliovaios; N. Stefanou (Physical Review B, 2022)
A time Floquet transfer-matrix method for the description of acoustic wave propagation through dynamic stratified structures, modulated by another, low-frequency, pump acoustic wave, is reported. The method is applied to a specific example of a GaAs/AlAs periodic superlattice, subject to a spatiotemporal modulation induced by an evanescent pump wave with frequency in the lowest acoustic band gap of the structure. By means of systematic numerical calculations, we provide compelling evidence for the occurrence of significant nonreciprocal transmission of an acoustic signal with frequency in a high-order acoustic band gap, through inelastic multiple-scattering processes. Our results indicate a promising route to design nonreciprocal acoustic devices.